The (Female) Graduate: Choice and Consequences of Women’s Clothing - Fasoli, Fabio; Maass, Anne; Volpato, Chiara; Pacilli, Maria Giuseppina (Frontiers in Psychology, 2018)
This research investigates how female students choose their graduation outfit and how clothing affects observers’ judgements. In Study 1, we manipulated the students’ graduation outfit so as to look professional or sexy. Female peers, adults, and professors formed a first impression about the students, their thesis work and guessed their graduation scores (thesis points and final mark). All participant groups judged the professionally dressed students as more competent, as having put more effort in their thesis, and as having obtained better scores than when the same students dressed sexy. In Studies 2 and 3 we replicated previous findings by using photos portraying real students in their actual graduation outfits. We found that sexy clothing, considered inappropriate for the occasion, affected estimated and actual graduation scores negatively and that this effect was mediated by perceived incompetence. Results are discussed with respect to women’s evaluation on the basis of their appearance.